AR Module for Learning Changes of Matter in Chemistry - Solomon Mahanan, Mangai; Ibrahim, Nor Hasniza; Surif, Johari; Ken Nee, Chee (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Internal Visualization challenges concerning sub-microscopic particles in chemistry often result in some difficulties in learning the change of state of matter. Therefore, this study aims at developing an augmented reality ProCAR module that utilizes a project-based learning approach to facilitate learning changes of matter. This study employs ADDIE (Analysis, Design, Development, Implementation and Evaluation) instructional design model. The quality of the module was evaluated by a group of 5 Chemistry teacher-educator experts of Universiti Teknologi Malaysia to identify the suitability of the module. Inter-rater reliability (IRR) percentages were determined and the feedback was analyzed based on thematic analysis. The result shows that 100% of its learning objectives, Content, Usability, and Assessment and 75% of its performances were good and reliable all having IRR value 75% and above. Such revealed that AR Module is potentially effective for the teaching phase change to Secondary school students.  Recommendations for future studies were highlighted